Studi Kasus Penerjemahan Teks Eksplanasi Menggunakan Metode Penerjemahan Semantis-Komunikatif pada "Routledge Handbook on Sufism" - Melinda Awalukita; Afriliani Afriliani (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2022)
Explanatory text is a text that explains the process related to natural, social, and cultural phenomena on a certain theme which is equipped with an explanation (Karnedi, 2014). This scientific work is presented as a case study of translating an explanatory text with a religious theme from the source language to the target language using the communicative-semantic translation method supported by a number of annotations related to the translation procedure. The annotation focuses on various spiritual, social, and cultural aspects of the book entitled Routledge Handbook on Sufism in the section on Sufism in Modern Morocco by Marta Dominguez Diaz. The purpose and benefit of writing this scientific paper is to provide an explanation of the translation of the beginning of a sociocultural phenomenon in the world of Islamic mystics that can develop in the country of Morocco at the end of the eighteenth century until today. The purpose of writing is to make it easier for readers to understand terms in spiritualist texts, as well as additional insight into the process of translating an explanatory text with a religious theme.   Teks eksplanasi adalah teks yang menerangkan proses berkaitan dengan fenomena alam, sosial, dan budaya atas tema tertentu yang dilengkapi dengan sebuah penjelasan (Karnedi, 2014). Karya ilmiah ini disajikan sebagai sebuah studi kasus penerjemahan teks eksplanasi bertema religi dari bahasa sumber ke bahasa sasaran dengan menggunakan metode penerjemahan komunikatif-semantis yang didukung dengan sejumlah anotasi terkait prosedur penerjemahannya. Anotasi menitikberatkan berbagai aspek spiritual, sosial, dan kultural dari buku yang berjudul Routledge Handbook on Sufism pada bagian Sufism in Modern Morocco karya Marta Dominguez Diaz. Tujuan dan manfaat dari penulisan karya ilmiah ini adalah untuk memberikan penjelasan penerjemahan tentang awal mula sebuah fenomena sosiokultural dalam dunia mistikus Islam dapat berkembang di negara Maroko di akhir abad kedelapanbelas hingga hari ini. Tujuan penulisan untuk memudahkan para pembaca dalam memahami istilah-istilah dalam teks spititualisme, serta sebagai wawasan tambahan mengenai proses penerjemahan suatu teks ekpslanasi bertema religi.